Genocide and resistance Nr. 7(1) - Jonušauskas, Laurynas; Dapkutė, Daiva; Banionis, Juozas; Kuizinienė, Dalia; Lebedeva, Natalija; Kangeris, Karlis; Bubnys, Arūnas; Jegelevičius, Sigitas; Knezys, Stasys (Genocidas ir rezistencija, 2000)
Full Issue (paper copy scan)